Proje yönetimi - Ganioğlu, Alirıza (Fen Bilimleri Enstitüsü, 1991)
Proje yönetimi; projenin programlanması, kontrol edilmesi ve gerekli olunduğunda değiştirilmesi için kullanılan dinamik bir metodlar ve teknikler setidir. Proje yönetimi sürekli olarak gelişerek, organizasyonel tasarım stratejisi haline gelmiştir. Sürekli gelişen teknoloji ve rekabet ortamının getirdiği yüklere proje yönetimi cevap ve çözümler getirmektedir. Proje planlama ve kontrol metodları denildiğinde; akla gelen ilk kavram CPM/PERT1 dir. Esas itibariyle CPM/ PERT bazlı pek çok metod mevcuttur. Proje yönetimi; proje teklifinin hazırlanmışı, maliyet tahminleri, fiyat tesbiti kaynak programlama ve satmalına gibi bir çok konuyu içermektedir. Projenin tamamlanmasından sonra veya proje devam ederken yapılan başarı ve performans analizleri de proje yönetiminin önemli bir konusudur. Proje yönetiminde dikkat edilmesi gereken bir unsur; insandır. Bu nedenle proje yönetimine psikometrik bir boyut kazandırmak gerekir. Organizasyonlar ve proje timleri oluşturulurken bu nokta özellikle ele alınmalıdır.

Project is a systems work that has a specific aim of which the inter-related activities are fulfilled during a definite period and generally for once. The aim in project planning may be divided into there main concepts: 1- Completion of the project with the available sources and within the shortest possible time, 2- Completion of the project by utilization of the minimum volume of sources within the pre-detennined project duration, 3- Completion of the project within the shortest possible period that will allow the minimum total project cost. The management chooses the most suitable concept mentioned above for its aims and by listing in line the activities forming the project makes the project plan. In order achieve those activities enlisted in parallel and/or series, the probable duration of these activities, requirement of sources and the priority ranks of these activities among themselves are taken into consideration. Some data acquirement is necessary for the planning of a project. These are as follows: - What kind of activities will the project include, - The inter-relations of these activities in terms of priority, succession, - The periods and cost of these activities, - The kinds of sources to be utilized during these activities, - The kinds and tybes of the apparatus and equipment that will be utilized and their capacities, xv Should these data not determinable spacificly they should be at least estimated. Estimation is an important factor at the period of project management. Correct esti mates made initially lead to good management control and moreover it will determine the risk of pricing and increase the effectiveness of the source related work. Numerous criteria is involved in the means of fulfilment of the project in accordance with the budget and programme. Projects may not be completed according to the laid by the budget and programme if the programme is over optimistic. Besides if there be continuous changes in the work field the efficient and effective control and monitoring of the project will be difficult. Preparation and following up suitable control procedures will make the control procedures will make the control of the costs more feasible so that the project may be completed. A good project control requires discipline. Project supervision includes the activities that will ensure the compatibility of the project application to the theoretical project; it also allows adaptations of the situations that are not covered in the plan. Supervision is a feedback mechanism. Should there be differences betwen the planned activities and those fulfilled, the causes are investigated and precautions are recommended. The aim of the precaution is to dissolve and diminish the difference between those planned and those fulfilled. If the planned target looses its verification a new target should be determined. Should the project target is accepted as verifiable such target should be maintained. However some amterations might be made on procedures leading to the target. These alterations made in the project plan is called up-to-dating. As a result project management is the provision, effective utilization and management of the following sources in sufficient quantities required qualities and at the right time: - Finance, - workforce - Materials - Equipment, - Technical and administrative personnel, First systematic approach to project planning and supervision occurred during the 1st World War in military xvi applications as Gantt chartes. Later Gantt charts are developed and their fields of applications are widened. Gannt charts are bar charts in general. Gantt diagrams are developed to show the relationship between tne elementary processes and operations taking into account the time and cost factors. The real development in Project planning and supervision took place ih 1950 ' s with the effect and contributions of operational research. The final approach is network approach. In this approach a project network reflecting the priority and succession of the activities among themselves is cons tructed. Crithical path in network analysis is the longest path through tne network that determines the project time. The activites on this path are called critical activities. Any delay in the activities on the critical path will delay the completion of the project on an equal time. Upon the determination of the critical path the activities that form bottlenecks and the activities that may be delayed without delaying the total project time and the period such activities may be delayed without causing any hinderance to the project may be shown. The project plan when designed spacifies the source requirements in terms of quantity time and duration. The activities on the path may be shifted to achieive the equal distribution of the source requirements during the project duration. This is called resource balancing. The basic assumption in a resource balancing problems is that there are unlimited quantity of all types of resources available. However in real life this assumption is not true. The resources available are limited. Under these circumstances, the activities that are not included on the critical path route, sometimes those even on the ciritical path are shifted so that the resource requirements in a specific time interval to not exceed the resources which are limited. When achieving this the elongation of the critical path is tried to be kept as minimum as possible This is titled limited resource allocation problem. The cost of each activity may be expressed as a function of period of activity. The total cost of the project which consists of direct and indirect cost may change with respect to project period. The project period which appears as the critical path period is changed and the mi nimum total cost is searched for. This change is mainta ined by shortening the periods of the critical activities as per a specific arrangement and legthening in some rare. Network approach consists of the following factors: i) Construction of the project network, ii) Finding the critical path, xvii iii) Resource analysis, iv) Time/Cost analysis, v) Supervision (control), vi) Up - to-dating, The first samples of the network approach are PERT (Periodic Evaluation and Review Technique) used for the coordination of the activities in the production of the Polaris missiles in 1957-1958 U.S. A and CPM (Critical Path Method) developed independent of PERT in France during the same period. The basic difference between PERT and CPM lies on the grounds and aim of developing these. PERT accepts some undistinction in the activity times combining the project duration and requests the most optimistic and pessimistic activity times besides the porbable activity time. This is the result of the lack of application in real life situations of the PERT project activities previously. On the contrast in CPM previous application regarding the project activities in considered to be sufficient and therefore only one activity time for each projecty is required. In the first CPM applications the delay punishments were very heavy which resulted in making the time factor very important and accordingly time/cost analysis were developed as an integral part of CPM. Generally, for the cases where the lack of application of PERT created undistinction, CPM were utilised in the project activities where a wide past application experience was available, However with the inclusion of the theoretical and prac tical developments both the two methods, the two methods became very similar to each other. Today CPM/PERT method is frequently mentioned. Though the fields of applications are different in general, the joint features of the CPM/PERT applicable projects are briefly as follows: - The projects consist of specifically described activities where the completion of these activities lead to the completion of the whole project. - Activities follow a specific sequence. - Activity durations are known or estimated initially. - An activity once started is completed uninterrup tedly. xviii - An activity may not start before the completion of the previous activity. However if such activity is not included on the critical path, it should not necessarily start soon after the previous activity is completed. That is its commencement might be delayed. Project management is the set of tecniques, methods and principles utilized for the control, amendment (when necessary) and programming of the project. The basic principle in project management is the construction of this set which consists of the graphics drawings and aims to achieve accurately described target. These graphics drawings Cpm or PERT netvork charts, Gantt charts, resource utilization tables and many other diagrams, figures and tables. On the other hand programming, resource alloca tion and project management techniques used in following- up budget are effective to the rate of the effectiveness of the project target/final product's original description Therefore the project target must be described in numeral terms. Besides should the project target not described properly the forecasts and estimates will not reflect the truth. Project plan is a device that changes versus time and is a dynamic device. After developed, the project plan will be re-examined due to causes of causes of change of the employees and means of activities, external limita tions etc. The project manager is in a position to manage the project and the personnel who indirectly are involved in the project. Project must include the following; - The project must contain the set of well described tasks that will successfully fulfill the project target. - The project must include activities that start and finish independently. - It must also include activities that may be arranged in order and that may be scheduled. Within the life-span of the project, the top mana gement shall initially fix the project aim. Later the time period estimates, the cost estimates and quality standards will be taken into consideration and discused. During this stage everybody everybody should accept that the tesk in process is nothing but an estimate. As the project work develops the estimates will be refined and xix clarified. By the proceeding of the project the estimates are re-considered and the project management methods will be revised. This refining process generally commences after the primary design stage is completed. Project mana gement process is given in figure S.l briefly As the work progresses periodically, position reports should be made concerning human resources, cost and specifications. Variances are calculated, the possible amendments are considered on the integrated plan. These amendments will be made to; - Widen time estimates, - increase the budget amount for the costs of human resources and additional equipments, - Modify the quality or the fields of activity of the final product by modifying the concept of the final product or by delaying the tasks. Aliwing some time for the minor unfinished details of the project to be completed when the project (final product) is finished a re-evaluation stage covering the calculations is proceeded. In this stage, the actual time money invested in the project and real quality is re evaluated. These data not only determines the success or failure but also forms a valuable data base for the future projects. The main aim in project management is to put forth efforts to achieve minimum project period, cost and resources. However it is obvious that it is difficult to achieve the minimum values of all these three factors. In general, project management creates the following benefits, - A clarified information is gathered for the project as a whole. - Project costs become controllable. - Intervenening needs to specific activities are know to effect the project. - Project critical points are determined. - Optimal utilization of the production resources and factors are maintained. xx CO 10 0) ü o u CM 4J fi 0) E 0) £7> tö fi fC S ?p o (U -n O M Cfl 0) ı-H XI m EH I I I I I I XXI The aim in broader sense of this thesis is to ensure that project managament gains a general view of the topic and to emphasize the main concepts in this subject. In this study all the periods from the tendering stage of the project to the completion period are closely examined separately. In this research as many as possible examples are tried to be given and explained. After project management in general is examined, some important aspects regarding this were handled of which "Project Team" comes first. An effective project team make considerable contributions to a successful project. It is obvious that a project team consisting of individuals who are just introduced to each other will have personal conflicts which effect the project. This subject is covered in a separate chapter, In the succeadeng chapters, the main project management methods were explained briefly and information in relation with project management development were provided. In the last chapter, project programme practice used during tne factory installations of "DUSA Industrial Yarn Establishments Co. Inc.".
Project management
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1991
Keywords: Proje yönetimi; Project management